1988
DOI: 10.1210/mend-2-8-756
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the 90-Kilodalton Heat Shock Protein is Associated with Tubulin-Containing Complexes in L Cell Cytosol and in Intact PtK Cells

Abstract: It has been established that the 90-kilodalton murine heat shock protein, hsp90, is associated with the untransformed, non-DNA-binding form of the glucocorticoid receptor in L cell cytosol. In this work, we show that incubation of L cell cytosol with Affi-Gel-coupled monoclonal antibodies directed against either alpha-tubulin alone or both alpha- and beta-tubulin results in the immune-specific adsorption of hsp90 identified by Western blotting with the AC88 monoclonal antibody. Similarly, the AC88 antibody, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 26 publications
1
45
0
2
Order By: Relevance
“…Alternatively, the role of hsp90 may be more passive in simply maintaining the inactive state of the receptor until hormone-dependent activation occurs. Another possible role of hsp90 has been suggested by Sanchez et al, who observed an association of hsp90 with microtubules (49). They suggested that this represents an intracellular trafficking system for transporting receptors to their sites of action.…”
Section: Discussionmentioning
confidence: 84%
“…Alternatively, the role of hsp90 may be more passive in simply maintaining the inactive state of the receptor until hormone-dependent activation occurs. Another possible role of hsp90 has been suggested by Sanchez et al, who observed an association of hsp90 with microtubules (49). They suggested that this represents an intracellular trafficking system for transporting receptors to their sites of action.…”
Section: Discussionmentioning
confidence: 84%
“…In cells, they form complexes with each other and additional proteins (20). Therefore, it was important to see whether Hsp 71 and Hsp 86 each bound Taxol independently or by means of bridging proteins (20)(21)(22). Purified bovine Hsc 73, the homolog of Hsp 71 (86% amino acid identity), and pure, recombinant human Hsp 90␣, the homolog of Hsp 86 (99% amino acid identity), were incubated alone or together in the presence of biotinylated Taxol, and the complexes were purified on monomeric avidin-agarose beads.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to interact with steroid receptors (6,38,41), with a variety of protein kinases (4,24,25,33), and with actin (18) and tubulin (37). Some evidence exists for its possible function as a protein kinase (9,28), and one report indicates a molecular chaperone activity of hsp90 in protein renaturation in vitro (52).…”
Section: Discussionmentioning
confidence: 99%